Prevalence and Antibiotic Susceptibility of Salmonella Strains Isolated from Viscera of Quail (Coturnix coturnix japonica) Breeds in Bingerville Area, Côte d’Ivoire - Bonny, Aya Carole; Assandi, Riviere; Karou, Tago Germain (European Scientific Journal, ESJ, 2019)
The control of food products contamination by Salmonella has become essential for the consumer to ensure the safety of these foods. Poultry meat and eggs play an important role as infection risk factors related to Salmonella strains resistant to antibiotics. Quail breeding, which is becoming to be appreciated by the Ivoirian population after chicken meat, may contain Salmonella pathogenic strains. Thus, a preliminary survey in two areas of high quail production (ANNA and SANTAI) in the city of Bingerville (Côte d’Ivoire), allowed collecting 60 viscera of quail for microbiological analysis. The microbiological analysis revealed 25 strains of Salmonella isolated from 11 viscera, resulting in a prevalence rate of 18.33 %. These strains also showed high resistance to Tetracycline (100 %), a relatively average resistance to Nalidixic acid (24 %) and low resistance to Ampicillin (8 %), Ticarcillin (8 %) and Cotrimoxazole (8 %). The presence of antibiotic-resistant strains of Salmonella in quail viscera could constitute a public health problem.